2022
DOI: 10.3389/fvets.2022.842105
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Somatic Cell Counts and Mammary Gland Parenchyma Ultrasonography in Buffaloes

Abstract: The aim of the present study was to determine whether the echotextural features of the mammary gland parenchyma in buffaloes during lactation at different somatic cell levels could be used to diagnose mastitis. This study was divided into two parts. In the first experiment, experimental buffaloes (n = 65) with somatic cell counts (SCC) tests (n = 94) in different seasons, including spring (n = 22), summer (n = 24), autumn (n = 37), and winter (n = 11), were used to obtain ultrasonic variables for each quarter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Ultrasound scanning of the mammary parenchyma at hour 72 after Staphylococcus infection showed a large range of hyperechoic areas, the lactiferous ducts became quite narrow, and the anechoic blood vessels could not be displayed [ 11 ]. Zhang et al [ 39 ] used computer-assisted technology to quantify the texture of udder ultrasound images and found that there was a positive correlation between the pixel standard deviation of udder ultrasound texture and the SCC level, indicating that, as the mastitis became increasingly severe, the pathological manifestations corresponding to the ultrasound texture became more obvious. The report by Abdullah et al [ 40 ] found that, as mastitis intensifies, the average numerical pixel values and pixel heterogeneity of the udder parenchyma echotexture increased.…”
Section: Resultsmentioning
confidence: 99%
“…Ultrasound scanning of the mammary parenchyma at hour 72 after Staphylococcus infection showed a large range of hyperechoic areas, the lactiferous ducts became quite narrow, and the anechoic blood vessels could not be displayed [ 11 ]. Zhang et al [ 39 ] used computer-assisted technology to quantify the texture of udder ultrasound images and found that there was a positive correlation between the pixel standard deviation of udder ultrasound texture and the SCC level, indicating that, as the mastitis became increasingly severe, the pathological manifestations corresponding to the ultrasound texture became more obvious. The report by Abdullah et al [ 40 ] found that, as mastitis intensifies, the average numerical pixel values and pixel heterogeneity of the udder parenchyma echotexture increased.…”
Section: Resultsmentioning
confidence: 99%
“…In our multivariable model (Table 4), quarter SCS was significantly associated with NPV, PSD, Gradient Mean Value, Homogeneity, Gradient Variance and Entropy, whilst udder quarter and time were significant, too. The authors of [12] studied buffaloes and also found that echotexture features (NPV and PSD) were significantly affected by SCC, lactation stage, scanning plane and udder quarter. These results indicate that echotexture analysis could aid the detection of subclinical mastitis-induced alterations of the mammary parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Echotexture analysis employs statistical features, such as mean Numerical Pixel Values (NPV) and Pixel Standard Deviation (PSD)-which are first-order echotexture features-to quantify parenchymal changes depicted in grey-scale images (B-mode sonograms) due to the presence of milk or under pathological conditions [10,11]. In buffaloes, first-order echotexture features were significantly correlated with milk somatic cell count (SCC) [12]. Furthermore, second-and higher-order echotexture features have been used in udder echotexture analysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…The image resolution as well as the sound waves' depth of penetration into the tissues depend on the probe's frequency (Williams, 2002;Silva et al, 2006;Fasulkov 2012); lower frequencies produce less resolution but have greater depth of penetration (Lucas et al, 2014). Various studies in large and small ruminants also evaluated the potential influence of the scanning plane on the echotextural characteristics of the mammary gland (Schwarz et al, 2020;Murawski et al, 2019;Zhang et al, 2022). However, there has been no information on the effect that scanning plane may have on the quantitative relationships between mammary echotexture and milk parameters in ewes.…”
mentioning
confidence: 99%